Setting profitable prices : a step-by-step guide to pricing strategy--without hiring a consultant - Jensen, Marlene (Hoboken, N.J. : John Wiley & Sons, 2013)
Time-tested strategies for making the best possible pricing decisions and gaining an unbeatable competitive advantage Pricing is one of the most important-and difficult-marketing problems companies face when launching new products. Unfortunately, the research that goes into making optimal pricing decisions is a very time-consuming process-unless, that is, you can afford to pay a consultant or outside agency to do it for you. But if you're like most small- to medium-sized business owners and managers, time and money are two things you absolutely don't have to spare. Problem solved: Written by a nationally recognized pricing expert, this book arms you with proven strategies for guaranteeing that you'll never again leave money on the table when determining prices. And you'll spend the least possible time setting your more profitable prices. Packed with valuable worksheets and other valuable tools to help guide your research and your pricing decision-making A goldmine of expert tips for pricing in any specialty market, it offers a highly effective way to market your company's product more effectively and profitably Shows you how to avoid making your competitors' pricing mistakes and gain a powerful competitive edge in the process The author uses examples drawn from her years of consulting work with companies large and small, including Food Network, American Express Publishing, and Playboy.
pt. 1. How to set prices for maximum profits -- pt. 2. How the market will value your new product -- pt. 3. Your cost analysis -- pt. 4. Fine-tuning your price -- pt. 5. Testing your prices -- pt. 6. Pricing in special situations.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Pricing; BUSINESS & ECONOMICS / Sales & Selling / Management; Pricing; Prisfastsættelse; Electronic books; Electronic books